Organizational myopia : problems of rationality and foresight in organizations - Catino, Maurizio (Cambridge : Cambridge University Press, 2013)
"Could the terrorist attacks on the Twin Towers have been avoided? What about the recent global financial crisis? Behind these apparently very different events it is possible to identify a common element of organizational myopia - a syndrome that severely limits the capacity of organizations to foresee the effects of their own decisions and to recognize signs of danger or opportunity. Based on several case studies, Organizational Myopia explores the barriers that impede organizations from identifying an effective response to the problems which they have to confront. Using real-world cases, the author investigates the mechanisms that generate myopia in organizations at the individual, organizational and interorganizational level in contexts that are complex, uncertain, ambiguous and changeable. This book will help readers understand how to limit the origins of myopia and therefore increase the capacity of organizations to anticipate and contain unexpected events"--
Machine generated contents note: Introduction; 1. Cases of myopia; 2. Uncertainty and predictability in organizations; 3. The mechanisms of organizational myopia; 4. Anticipating risk: the problem of learning; 5. Implications for organizational design; Epilogue.
Includes bibliographical references (pages 221-245) and index.
Keywords: Organizational learning; Organizational behavior; BUSINESS & ECONOMICS / Organizational Behavior